Whole genome-based reclassification of several species of the genus Nonomuraea - Bouras, Noureddine; Nouioui, Imen; Dif, Guendouz; Chaouch, Fawzia Chaabane; Ebada, Sherif S. (PloS one, 2025)
Earlier classification methods lacked the resolution necessary to delineate species comparing to current standards, particularly since a significant number of bacterial taxa were described before the integration of whole-genome sequencing into microbial taxonomy. With the advent of genome-based taxonomic approaches and integrated genomic metrics, including sequence similarity and phylogenomic frameworks, it has become essential to reevaluate the taxonomic status of older taxa defined before the era of genome-based microbial taxonomy. Applying these modern genomic criteria enables a more accurate assessment of species boundaries and helps to determine whether the old taxa represent distinct species or should be reclassified as synonyms, subspecies, or members of different genera. Such reclassification efforts are crucial for ensuring taxonomic accuracy, improving the reliability of comparative genomics, and maintaining stable and evolutionariy meaningful nomenclature. In this study, we re-evaluated the taxonomy of Nonomuraea using genome-based methods, including digital DNA-DNA hybridization (dDDH), average nucleotide identity (FastANI), average amino acid identity (AAI), and percentage of conserved proteins (POCP) analyses, complemented by phylogenomic analysis. Based on comprehensive genomic studies, our results support the elevation of both Nonomuraea roseoviolacea subsp. carminata and Nonomuraea roseoviolacea subsp. roseoviolacea to an unified species without subspecies distinction: Nonomuraea roseoviolacea (ATCC 27297 T = BCRC 13406 T = CBS 260.72 T = CCM 3491 T = CCRC 13406 T = CGMCC 4.1072 T = CIP 106924 T = DSM 43144 T = IFO 14098 T = IMET 9751 T = JCM 3145 T = KCTC 9283 T = NBRC 14098 T = NCIB 11117 T = NCIMB 11117 T = NRRL B-16127 T = VKM Ac-909 T ). Furthermore, we propose the reclassification of Nonomuraea recticatena , Nonomuraea roseola and Nonomuraea dietziae as subspecies within N. roseola . Consequently, we propose the establishment of the following two subspecies: Nonomuraea roseola subsp. roseola subsp. nov. (= ATCC 33579 T = DSM 43767 T = DSM 44323 T = IFO 14685 T = IMET 9576 T = INA 1671 T = JCM 3323 T = KCTC 9282 T = NBRC 14685 T = VKM Ac-1180 T ) and Nonomuraea roseola subsp. recticatena subsp. nov., comb. nov. (= DSM 43937 T = IFO 14525 T = INA 308 T = JCM 6835 T = KCTC 9279 T = NBRC 14525 T = VKM Ac-940 T ) and. In addition, we propose Nonomuraea harbinensis as later heterotypic synonyms of Nonomuraea ferruginea.